Vasorelaxant Effects Induced by Red Wine and Pomace Extracts of Magliocco Dolce cv. - Gabriele Carullo; Amer Ahmed; Fabio Fusi; Fabio Sciubba; Maria Enrica Di Cocco; Donatella Restuccia; Umile Gianfranco Spizzirri; Simona Saponara; Francesca Aiello (MDPI AG, 2020)
Several epidemiological studies demonstrate that moderate (red) wine consumption may afford protection against cardiovascular diseases. Protection is ascribed to the biological activity of wine components, many of which, however, are discarded during winemaking. In vitro rat thoracic aorta rings contracted with phenylephrine or KCl were used to assess the vasorelaxant activity of extracts from wine pomaces (seeds and skins) of the Calabrian autochthonous grape variety Magliocco dolce (Arvino). NMR spectroscopy was used to ascertain their chemical composition. Data demonstrate that seed and skin, but not must, extracts are capable of relaxing vascular preparations in an endothelium-dependent manner, similarly to the red wine extract, due to the presence of comparable amounts of bioactive constituents. In rings pre-contracted with 20-30 mM KCl, only seed extracts showed a moderate relaxation. The most efficacious vasodilating extract (wine) showed a good antioxidant profile in both [(2,2-diphenyl-1-picrylhydrazyl)acid] radical (DPPH) and [2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid)] radical (ABTS) assays. In conclusion, winemaking from Magliocco dolce grape can provide potentially health-promoting by-products useful in cardiovascular disease management.